2001
DOI: 10.1006/dbio.2001.0200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chordin-like Protein Inhibitor for Bone Morphogenetic Proteins Expressed Preferentially in Mesenchymal Cell Lineages

Abstract: Chordin is a bone morphogenetic protein (BMP) inhibitor that has been identified as a factor dorsalizing the Xenopus embryo. A novel secreted protein, CHL (for chordin-like), with significant homology to chordin, was isolated from mouse bone marrow stromal cells. Injection of CHL RNA into Xenopus embryos induced a secondary axis. Recombinant CHL protein inhibited the BMP4-dependent differentiation of embryonic stem cells in vitro and interacted directly with BMPs, similar to chordin. However, CHL also weakly b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(116 citation statements)
references
References 62 publications
4
112
0
Order By: Relevance
“…For example, physical association studies showed that chick CHRDL1 binds to BMP4 but not to BMP7, 46 whereas mouse and human CHRDL1 bind to BMP4 49 and mouse CHRDL1 to BMP5 and BMP6. 47 In a functional osteoblast differentiation assay, rat CHRDL1 binds to and antagonizes BMP7 but not BMP2. 50 In our studies, we demonstrate that human CHRDL1 binds BMP7 in the presence of TWSG1 and ascribe a function to human CHRDL1 similar to that reported for rodent CHRDL1.…”
Section: Discussionmentioning
confidence: 99%
“…For example, physical association studies showed that chick CHRDL1 binds to BMP4 but not to BMP7, 46 whereas mouse and human CHRDL1 bind to BMP4 49 and mouse CHRDL1 to BMP5 and BMP6. 47 In a functional osteoblast differentiation assay, rat CHRDL1 binds to and antagonizes BMP7 but not BMP2. 50 In our studies, we demonstrate that human CHRDL1 binds BMP7 in the presence of TWSG1 and ascribe a function to human CHRDL1 similar to that reported for rodent CHRDL1.…”
Section: Discussionmentioning
confidence: 99%
“…Chrdl1 is a Bmp antagonist that binds to BMP4 and BMP6 but not BMP5 and Activin. In contrast to Chordin, Chrdl1 weakly interacts with TGFb1 and TGFb2 (9). Neuralin 1 was identified in the human genome by a homology-based search (23).…”
Section: Cysteine-rich Domains In Chordinmentioning
confidence: 99%
“…Chrdl1 and Chrdl2 inhibit BMP signaling by binding directly to BMPs (9,10). Although Brorin and Brorin-like also inhibit BMP signaling, it is unclear whether they bind to BMPs (11, 12).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations